ANALISIS PERAN KEPEMIMPINAN KEPALA BAZNAS KABUPATEN KARAWANG - Rizky Maulana; Syifa Pramudita Faddila (PT Naureen Digital Education, 2023)
Leadership role is the ability/expertise of a person who can influence and can motivate others to do something according to a common goal. Another definition of leadership is a set of behaviors that are expected to be carried out by a person according to his position as a leader. The role of leadership includes the process of influencing in determining the organization or institution, motivating the behavior of followers to achieve goals, influencing to improve the group and culture his. This study aims to analyze the leadership role of the head of BAZNAS Karawang Regency. This research is the result of field research using qualitative methods. Data collection techniques in this study are: observation and interviews. The conclusion from the results of this study is that leadership role applied by BAZNAS Karawang Regency is to prioritize brotherhood between employees with other, so as to form a cohesiveness of the performance. In the context of communication, the head of BAZNAS Karawang Regency applies a charismatic communication pattern so that the role of leaders like this will build management management quality performance by creating a pattern of communication that is well connected between superiors and subordinates. The Head of BAZNAS Karawang Regency in making decisions also took steps in deliberations where all the suggestions given from the work team without exception